Pengaruh Pendidikan, Pelatihan dan Pengetahuan Akuntansi Syariah Terhadap Kualitas Penyajian Informasi Akuntansi Syariah Di BMT Tulungagung - Iqbalur Rusydi; Sri Dwi Estiningrum (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to determine the effect of sharia accounting education, training and knowledge on the quality of presentation of sharia accounting information at BMT in Tulungagung. The method used in this research is quantitative with associative research. The sampling technique used purposive sampling and used the slovin formula, which obtained a sample of 34 respondents and 31 data that could be processed. Data analysis in this study used validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of this study show that partially the education and training variables have no effect on the presentation of accounting information at the BMT in Tulungagung, while the sharia accounting knowledge variable has a significant positive effect on the presentation of sharia accounting information on the BMT in Tulungagung. Simultaneously the influence of education, training and knowledge of sharia accounting has a significant positive effect on the quality of presentation of sharia accounting information at BMT in Tulungagung.